2021
DOI: 10.1302/0301-620x.103b.bjj-2021-0549.r1
|View full text |Cite
|
Sign up to set email alerts
|

Radiographs of 366 removed limb-lengthening nails reveal differences in bone abnormalities between different nail types

Abstract: Aims Limb-lengthening nails have largely replaced external fixation in limb-lengthening and reconstructive surgery. However, the adverse events and high prevalence of radiological changes recently noted with the STRYDE lengthening nail have raised concerns about the use of internal lengthening nails. The aim of this study was to compare the prevalence of radiological bone abnormalities between STRYDE, PRECICE, and FITBONE nails prior to nail removal. Methods This was a retrospective case series from three cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
5
13
0
Order By: Relevance
“…However, they are limited in terms of comparability to other intramedullary lengthening systems. [8][9][10][11][12][13]15,21 This study was designed to provide a comprehensive approach in terms of clinical and radiological outcome of treatment with the conventional PRECICE and the STRYDE intramedullary lengthening nail. Compared to previous studies, a large and homogenous group of patients using a 2:1 matched-pair design was examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are limited in terms of comparability to other intramedullary lengthening systems. [8][9][10][11][12][13]15,21 This study was designed to provide a comprehensive approach in terms of clinical and radiological outcome of treatment with the conventional PRECICE and the STRYDE intramedullary lengthening nail. Compared to previous studies, a large and homogenous group of patients using a 2:1 matched-pair design was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Since a manufacturer recall in early 2021, multiple reports have demonstrated the presence of adverse tissue reactions in stainless-steel intramedullary lengthening nails [ 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 ]. In a report of three cases, Sax et al [ 19 ] demonstrated radiographic osteolysis in patients implanted with the stainless-steel nail with histologic confirmation of phagocytic activity of green-gold crystalline debris characteristic of metal debris.…”
Section: Discussionmentioning
confidence: 99%
“…They also found macroscopic corrosion at the modular junction in 83% of recipients, similar to that reported by our group in a previous publication [ 19 ] and a separate analysis of retrieved nails at another institution [ 30 ]. In a comparative study of multiple variations of an intramedullary limb lengthening nail, Iobst et al [ 29 ] observed a greater proportion of bone abnormalities at the modular junction of the STRYDE nail, as compared to the PRECICE or FITBONE (Orthofix Medical Inc., Lewisville, TX, USA). Given the current clinical understanding and relative dearth of data surrounding osteolysis at the modular junction of intramedullary limb lengthening nails, the existing reports are limited to descriptions of a pre-explantation process.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent report compares the radiological changes associated with patients following lengthening with a Stryde, Precice or Fitbone nail [38] . They confirmed 77% of Stryde nails (20/26) had bone changes as reported above, at the site of the nail telescopic junction.…”
Section: Innovation -The Stryde Lengthening Nail a Cautionary Talementioning
confidence: 99%